Computer-Aided Design in Subtractive and Additive Prototyping - Tang, Sai Hong; Wong, Su Luan; Sulaiman, Shamsuddin; Young, Paul; M. Saleem, J. Hashmi (Universiti Putra Malaysia Press, 2004)
This paper concerns the use of a commercially available computer-aided design software in designing and manipulating the complex-shaped models for subtractive and additive prototyping processes. In the subtractive prototyping approach, the computer-aided design software was used to create surface models. The models were section-cut into multiple cross sectional layers. Then, the section-cut models were converted from graphic files into non-graphic files (neutral format files). In the additive prototyping approach, the computer-aided design software was used to create solid models with internal cavities (parent model). Multiple smaller diameter solid models were then derived from the parent mode!. The various diameter solid models were converted into surface models. The surface models were then section-cut and later changed into neutral format files. The computer-aided design software used in the project was AutoSurf, a commercially available product of Autodesk, Inc. The hardware which was used ;n the above processes were a four degrees of freedom precision robotic manipulator (for manipulating raw material), a ball-nosed end milling device (in subtractive prototyping) and a semi-liquid deposition tool (for additive prototyping). This study revealed the possibility of using cheap and general computer-aided design software to accomplish the complex-shaped model design and manipulation work in the prototyping processes instead of using expensive rapid prototyping software.